Obserwacje dotyczące rozpowszechnienia germanizmów leksykalnych we współczesnym regiolekcie śląskim - Gerd Hentschel (Ksiegarnia Akademicka Publishing, 2019)
Observations on the Spread of Lexical Germanisms in the Contemporary Silesian Regiolect The article analyses the extent to which Silesians who say that they regularly use the Silesian regiolect still actively use the numerous lexical Germanisms that have been described for Silesian. It is based on a survey of nearly 1,000 respondents about their “subjective frequency” of Germanism usage. Procedures are suggested for distinguishing between Germanisms that tend to be used more frequently and those that tend to be used less frequently. A much-discussed codification of Silesian could dispense with the latter. Factors influencing usage frequency that are discussed in the article include the prevalence of a range of Silesian Germanisms in Polish dialects outside of Silesia as well as knowledge of German. In addition, the extent of Silesian and Polish usage by speakers of Silesian in different communication contexts is also described.